(untitled) (Politeja, 2020)
The article focuses on the issue of Croatia’s ethnic policy towards minorities at the level of administrative and territorial organization. It attempts to answer the question whether and to what extent the ethnic and territorial conflict in the 1990s influenced the processes of transformation of the administrative and territorial organization of the state. The Croatian state, given as an example, at the time of declaring its independence in 1991 had to face the threat of territorial disintegration from the Serb minority living in its territory. The Italian minority was also suspected of such tendencies, but it soon turned out that these suspicions were groundless. The Serbian community could, however, threaten the unification of the state, which initially happened as a result of an armed conflict. After its end, fears did not diminish, especially in the face of the changes in territorial borders that took place until the end of the first decade of the 21st century. The threat could be reduced using one of the tools, which was the local government administration and the shape of its territorial units. The Author analyses this issue basing on the projects of Croatian experts dealing with the issues of administrative and territorial organization of the last three decades and at various stages of Croatian statehood, data on demographic changes and laws regulating the functioning of local and regional local governments as well as regulations concerning the position of national minorities in the state.